DEVELOPING MULTIPLE INTELLIGENCES THROUGH ICT-BASED E-LEARNING PROGRAM - Mayub, Afrizal; Fahmizal, Fahmizal (IJIET (International Journal of Indonesian Education and Teaching), 2023)
This study aims to determine the development of nine types of intelligence (Multiple Intelligences) through an e-learning program implemented through a computer network and/or personal computer (PC) with CD ROM. This type of research includes quantitative descriptive research, which describes the function of e-learning programs as a means of growth and development of all types of intelligence. The research method is carried out by comparing the pedagogical way of developing multiple intelligences with the facilities owned by the e-learning program. The degree of conformity used a percentage (%), then processed using a Likert Scale. Based on theory and virtual experiments, as well as the opinions of 2 experts and 35 education practitioners as junior/high school teachers, it was found that the e-learning program functions to facilitate the development of intelligence in the "distributed" category with a score of 4 (scale 1-5). The results of this study will help teachers and lecturers reflect on face-to-face learning so that during the Covid-19 period learning can be transferred to a system that uses an e-learning program that can accommodate the growth and development of multiple intelligences supported by technological advances. Moreover, this system does not require a network and signal but can be accessed in the form of a CD-ROOM/Flash Disk. In the future, learning like this can be a priority to be implemented.